Method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol
By using nickel sulfide-nickel oxide composite nanosheet foam nickel sulfide and nitrogen-doped porous carbon support palladium nickel boron nanoparticle alloy as electrodes in acid-base mixed electrochemical electrolytic cells, the efficient electrochemical oxidation and reduction of phenol is achieved, and the high value-added products benzone and cyclohexanone are generated, which solves the problems of high cost, large energy consumption and low processing efficiency in the prior art, and has the advantages of high efficiency, environmental protection and economical.
Patent Information
- Application Number
- CN202410656022.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-24
- Publication Date
- 2025-03-14
AI Technical Summary
The existing phenol electrochemical oxidation or reduction technology has problems such as high cost, large energy consumption and low processing efficiency, and the reaction kinetics are slow, there are many intermediate products, complex reaction mechanisms, and low product selectivity.
The acid-base mixed electrochemical electrolytic cell is used, and the nickel foamed nickel sulfide-nickel oxide composite nanosheets are used as the anode, and the palladium-nickel boron nanoparticle alloy with porous carbon as the carrier is used as the cathode. The anode and cathode electrolyte are separated by a bipolar membrane, and electrochemical oxidation and reduction reactions are carried out at the anode and cathode respectively to generate high value-added products benzenequinone and cyclohexanone.
The efficient electrochemical oxidation and reduction of phenol is achieved, and the generated benzenequinone and cyclohexanone have high selectivity and Faraday efficiency. The electrochemical electrolytic cell operates at a small potential, has low energy consumption and high processing efficiency, and has the advantages of environmental protection and economicality.
Smart Images

Figure CN119615194A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol. Background Art
[0002] The sustainable development of human society depends on the continuous progress of efficient energy storage and conversion technologies. As "biomass energy" and "the only renewable carbon source", the selective upgrading of lignin and its derivatives into high-value-added chemicals and fuels is crucial to reducing dependence on traditional fossil fuels. Phenol poses a major threat to environmental safety due to its limited biodegradability and treatment sensitivity. This problem has been widely recognized in the global coal chemical industry and has become an obstacle to the sustainable development of the semi-coke industry. Traditional phenol treatment methods mainly include physical extraction and chemical degradation. Unfortunately, these methods have disadvantages such as low treatment efficiency and potential serious secondary pollution, which greatly limits their widespread application. Electrochemical oxidation or reduction technology provides a viable alternative for the green and economic degradation of phenol, effectively solving the problems of high cost, excessive energy consumption and poor treatment effect of traditional treatment methods. In addition, it also produces valuable high-value-added products such as benzoquinone and cyclohexanone. However, the electrochemical oxidation (EOP) or reduction (ECH) process of phenol involves multiple electron transfers and proton coupling, and the reaction system has problems such as slow kinetics, many intermediates, complex reaction mechanism and low product selectivity.
[0003] To address the above problems, the development of EOP and ECH electrocatalysts with high catalytic activity and high selectivity can achieve high-value utilization of phenol; at the same time, the energy conversion efficiency and stability of the electrolyzer can be further improved by optimizing the design of the electrolysis system. Summary of the invention
[0004] The purpose of the present invention is to provide a method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol in view of the problems of high cost, excessive energy consumption and low treatment efficiency of existing phenol electrochemical treatment technology.
[0005] To achieve the above purpose, the present invention adopts an acid-base mixed electrochemical electrolytic cell, with an alkaline electrolyte as an anolyte, an acidic electrolyte as a catholyte, a nickel foam loaded with nickel sulfide-nickel oxide composite nanosheets as an anode, and a palladium nickel boron nanoparticle alloy with a nitrogen-doped porous carbon as a carrier as a cathode. The anolyte and the catholyte are separated by a bipolar membrane, the anion exchange membrane of the bipolar membrane faces the cathode, and the cation exchange membrane faces the anode; phenol is added to the anolyte and the catholyte respectively, so that the anode electrochemically oxidizes the phenol to generate benzoquinone, and the cathode electrochemically reduces the phenol to generate cyclohexanone.
[0006] Furthermore, the cathode electrolyte is a 0.5-2 mol / L sulfuric acid aqueous solution, and the anode electrolyte is a 1-2 mol / L potassium hydroxide aqueous solution.
[0007] Furthermore, the molar ratio of the phenol added to the anolyte to the potassium hydroxide in the anolyte is 1:150-300, and the molar ratio of the phenol added to the catholyte to the sulfuric acid in the catholyte is 1:100-150.
[0008] Furthermore, the bipolar membrane is a Nafion membrane.
[0009] Furthermore, the resistance of the nickel foam loaded with nickel sulfide-nickel oxide composite nanosheets is less than 5Ω, the mass content of nickel in the nickel sulfide-nickel oxide composite nanosheets is 1% to 10%, and the loading amount of the nickel sulfide-nickel oxide composite nanosheets on the nickel foam is 1 to 4 mg / cm 2 The preparation method of the nickel foam loaded with nickel sulfide-nickel oxide composite nanosheets is as follows: immersing the nickel foam in an aqueous solution containing nickel nitrate, ammonium fluoride and urea, ultrasonicating for 10 to 30 minutes, placing the nickel foam in a reactor for hydrothermal reaction at 90 to 120° C. for 10 to 12 hours, taking out the nickel foam after the reaction, drying it, and calcining it at 300 to 400° C. for 1 to 3 hours in an inert atmosphere, and then placing the calcined product together with a sodium sulfide aqueous solution in a reactor for hydrothermal reaction at 120 to 140° C. for 10 to 14 hours to obtain the nickel foam loaded with nickel sulfide-nickel oxide composite nanosheets; wherein the molar ratio of the nickel nitrate, ammonium fluoride, urea and sodium sulfide is 1:1.5 to 3:0.3 to 1:1 to 2.
[0010] Furthermore, the resistance of the palladium-nickel-boron nanoparticle alloy with the nitrogen-doped porous carbon as a carrier is less than 3Ω, and the loading amount of the palladium-nickel-boron nanoparticle alloy on the carrier is 10wt% to 40wt%. The preparation method of the palladium nickel boron nanoparticle alloy with nitrogen-doped porous carbon as a carrier is as follows: zinc nitrate hexahydrate and 2-methylimidazole are dissolved in methanol respectively, and after they are completely dissolved, the obtained 2-methylimidazole solution is injected into the zinc nitrate hexahydrate solution, stirred at room temperature, precipitated and centrifuged, washed with methanol and deionized water, and then vacuum dried to obtain a ZIF-8 precursor; the ZIF-8 precursor, an ethylene glycol solution of palladium acetylacetonate, and an aqueous nickel nitrate solution are mixed, ultrasonically treated to form a uniform solution, and then a sodium borohydride aqueous solution is added under vigorous stirring, and heated at 90-140° C. for reaction for 1-2 hours under a nitrogen atmosphere; after the reaction is completed, the palladium nickel boron nanoparticle alloy with nitrogen-doped porous carbon as a carrier is filtered and vacuum dried to obtain the nickel chloride, palladium acetylacetonate, sodium borohydride The molar ratio is 2-3:1:2-3.
[0011] Furthermore, the above method electrochemically oxidizes phenol at the anode to generate benzoquinone and electrochemically reduces phenol at the cathode to generate cyclohexanone at a voltage of 1.0 to 1.5 V vs. RHE.
[0012] The beneficial effects of the present invention are as follows:
[0013] The electrochemical electrolytic cell of the present invention is equipped with an acid and an alkali asymmetric electrolyte in the cathode cell and the anode cell respectively, and the chemical neutralization of the acid and the alkali is prevented by a Nafion membrane, and phenol is electrochemically reduced to generate cyclohexanone at the cathode, and phenol is electrochemically oxidized at the anode end to generate an additional product benzoquinone with high economic value. Under a relatively low potential of 1.30V vs.RHE, the Faraday efficiency of benzoquinone produced at the anode end is as high as 95% and has high selectivity, and the cathode end can achieve a phenol conversion rate of 98.9% and a cyclohexanone selectivity of 90.3% when reacting for 60 minutes. In addition, cyclohexanone and benzoquinone can be used as the products of the anode chamber and the cathode chamber respectively to realize closed-loop circulation, and the whole system only needs to consume acid and alkali, which has the advantages of good environmental protection effect and considerable production capacity. The electrochemical electrolytic cell used has good stability, a simple preparation method, low cost, is easy to realize large-scale production, and has the potential to be applied to large-scale treatment of acid and alkali wastewater containing phenol in industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic diagram of the structure of the electrochemical oxidation / reduction phenol electrolytic cell of the present invention.
[0015] Figure 2 This is the LSV curve of phenol reduction in a three-electrode system with palladium-nickel-boron nanoparticle alloy supported on nitrogen-doped porous carbon as the working electrode.
[0016] Figure 3 0.5M H2SO4 / 1M KOH-ECH / EOP represents phenol reduction coupled with phenol oxidation using the acid-base mixed electrochemical electrolytic cell of Example 1, 1M KOH / 1M KOH-ECH / EOP represents phenol oxidation coupled with phenol reduction under alkaline conditions, and 0.5M H2SO4 / 1M KOH-OER / ECH represents oxygen evolution under alkaline conditions coupled with phenol reduction under acidic conditions.
[0017] Figure 4 Graph showing the Faraday efficiency of cyclohexanone, a cathode product, in the electrochemical oxidation-reduction of phenol in Example 1.
[0018] Figure 5 This is a Faraday efficiency diagram of the anode product benzoquinone in the electrochemical oxidation-reduction of phenol in Example 1.
[0019] Figure 6This is a graph showing the relationship between the reaction time of reducing phenol to cyclohexanone in the electrochemical oxidation-reduction of phenol in Example 1 and the change in concentration.
[0020] Figure 7 1 is a graph showing the selectivity of phenol to cyclohexanone in the electrochemical oxidation-reduction of phenol in Example 1.
[0021] Figure 8 This is a stability test diagram of the electrochemical cell in Example 1. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the protection scope of the present invention is not limited to these examples. Unless otherwise specified, the raw materials in the examples are purchased through commercial channels.
[0023] Example 1
[0024] A 1cm×1.5cm nickel foam was immersed in a 45mL aqueous solution containing 0.58g (2mmol) nickel nitrate, 0.148g (4mmol) ammonium fluoride and 0.6g (1mmol) urea. After ultrasonic treatment for 20 minutes, the nickel foam was placed in a reactor for hydrothermal reaction at 110°C for 12 hours. After the reaction, the nickel foam was taken out, dried and calcined at 350°C for 2 hours under an inert atmosphere. The calcined product was then placed in a reactor together with 50mL 2.2g / mL (3mmol) sodium sulfide aqueous solution for hydrothermal reaction at 130°C for 12 hours to obtain a nickel foam loaded with nickel sulfide-nickel oxide composite nanosheets, the resistance of which was less than 5Ω, the atomic content ratios of Ni, S and O in the nickel sulfide-nickel oxide composite nanosheets were 47.27%, 5.10% and 47.62% respectively, the mass content of nickel in the nickel sulfide-nickel oxide composite nanosheets was 8%, and the loading amount of the nickel sulfide-nickel oxide composite nanosheets on the nickel foam was 1mg / cm 2 .
[0025] 3.0 g of zinc nitrate hexahydrate and 12.0 g of 2-methylimidazole were dissolved in 45 mL and 35 mL of methanol, respectively. After complete dissolution, the 2-methylimidazole solution was injected into the zinc nitrate hexahydrate solution and stirred at room temperature for 16 hours. The resulting precipitate was centrifuged and washed three times with methanol and deionized water, respectively, and then vacuum dried at 60°C for 10 hours to obtain a ZIF-8 precursor. 0.02g ZIF-8 precursor and 0.26mL ethylene glycol solution containing 1g (0.03mmol) acetylacetonate palladium and 1mL aqueous solution containing 0.2g (0.08mmol) nickel chloride hexahydrate were mixed and ultrasonically treated for 30 minutes to ensure the formation of a uniform solution; then, under vigorous stirring, 5mL aqueous solution containing 30mg (0.07mmol) sodium borohydride was slowly added to the above uniform solution, and then the resulting mixed solution was transferred to a 50mL round-bottom flask, and heated at 120°C for 1 hour under nitrogen atmosphere protection; after the reaction was completed, the product was filtered and dried at 60°C in vacuum for 24 hours to obtain a palladium nickel boron nanoparticle alloy (denoted as PdNiB@NC) with a nitrogen-doped porous carbon as a carrier, and its resistance was less than 3Ω. The loading amount of the palladium nickel boron nanoparticle alloy on the nitrogen-doped porous carbon carrier was 30wt%, and the atomic percentages of palladium, nickel, and boron in the palladium nickel boron alloy nanoparticles were 0.02%, 1.2%, and 2.26%, respectively.
[0026] like Figure 1 As shown, the anode chamber of the acid-base mixed electrochemical electrolytic cell of the present embodiment is 500mL 1mol / L potassium hydroxide aqueous solution, the cathode chamber is 500mL 0.5mol / L sulfuric acid aqueous solution, the anode is the nickel foam (1cm×1.5cm) loaded with the above-mentioned nickel sulfide-nickel oxide composite nanosheet, the cathode is the palladium nickel boron nanoparticle alloy (coated on 1cm×1.5cm carbon paper) with the above-mentioned nitrogen-doped porous carbon as a carrier, and the two chambers are separated by a Nafion membrane, wherein the anion exchange membrane of the Nafion membrane faces the cathode chamber and the cation exchange membrane faces the anode chamber. Phenol is added to the anode chamber and the cathode chamber respectively, so that the molar ratio of phenol to potassium hydroxide in the anode chamber is 1:200, and the molar ratio of phenol to sulfuric acid in the cathode chamber is 1:150, and the anode electrochemically oxidizes the phenol to generate benzoquinone at a voltage of 1.30V vs.RHE, and the cathode electrochemically reduces the phenol to generate cyclohexanone. According to the test, the Faradaic efficiency of benzoquinone generated at the anode is as high as 95% with high selectivity. After 60 minutes of reaction, the cathode can achieve a phenol conversion rate of 98.9% and a cyclohexanone selectivity of 90.3%.
[0027] Example 2
[0028] like Figure 1As shown, the anode chamber of the acid-base mixed electrochemical electrolytic cell of the present embodiment is 500mL 2mol / L potassium hydroxide aqueous solution, the cathode chamber is 500mL 0.5mol / L sulfuric acid aqueous solution, the anode is nickel foam (1cm×1.5cm) loaded with nickel sulfide-nickel oxide composite nanosheets, the cathode is palladium nickel boron nanoparticle alloy (coated on 1cm×1.5cm carbon paper) with nitrogen-doped porous carbon as a carrier, and the two chambers are separated by a Nafion membrane, wherein the anion exchange membrane of the Nafion membrane faces the cathode chamber and the cation exchange membrane faces the anode chamber. Phenol is added to the anode chamber and the cathode chamber respectively, so that the molar ratio of phenol to potassium hydroxide in the anode chamber is 1:200, and the molar ratio of phenol to sulfuric acid in the cathode chamber is 1:150, and the anode electrochemical oxidation of phenol generates benzoquinone at a voltage of 1.24V vs.RHE, while the cathode electrochemical reduction of phenol generates cyclohexanone.
[0029] Example 3
[0030] like Figure 1 As shown, the anode chamber of the acid-base mixed electrochemical electrolytic cell of the present embodiment is 500mL 1mol / L potassium hydroxide aqueous solution, the cathode chamber is 500mL 0.5mol / L sulfuric acid aqueous solution, the anode is nickel foam (1cm×1.5cm) loaded with nickel sulfide-nickel oxide composite nanosheets, the cathode is palladium nickel boron nanoparticle alloy (coated on 1cm×1.5cm carbon paper) with nitrogen-doped porous carbon as a carrier, and the two chambers are separated by a Nafion membrane, wherein the anion exchange membrane of the Nafion membrane faces the cathode chamber, and the cation exchange membrane faces the anode chamber. Phenol is added to the anode chamber and the cathode chamber respectively, so that the molar ratio of phenol to potassium hydroxide in the anode chamber is 1:200, and the molar ratio of phenol to sulfuric acid in the cathode chamber is 1:150, and the anode electrochemical oxidation of phenol generates benzoquinone at a voltage of 1.24V vs.RHE, while the cathode electrochemical reduction of phenol generates cyclohexanone.
[0031] In order to prove the beneficial effects of the present invention, the inventors further conducted the following experiments:
[0032] The palladium nickel boron nanoparticle alloy (coated with 1 cm×1.5 cm carbon paper) with nitrogen-doped porous carbon as the carrier in Example 1 was used as the working electrode, the carbon rod was used as the counter electrode, Ag / AgCl was used as the reference electrode, and 0.5 mol / L sulfuric acid aqueous solution was used as the electrolyte. Phenol was added to the electrolyte so that the molar ratio of phenol to sulfuric acid was 1:150. The electrocatalytic performance of the reduction of phenol was evaluated in a three-electrode system. At the same time, a comparative test was performed without adding phenol. The potential data was converted into the reversible hydrogen electrode (RHE) potential using the Nernst equation, and its E RHE =E Ag / AgCl +0.199V+0.059×pH, according to Figure 2The linear sweep voltammetry (LSV) curve shown in FIG. 1 shows that the palladium nickel boron nanoparticle alloy working electrode supported by nitrogen-doped porous carbon has a lower over-point and a smaller current density, and exhibits good electrocatalytic performance in the electrochemical reduction (ECH) reaction of phenol. In particular, it exhibits good hydrogen evolution (HER) activity in a 0.5 mol / L sulfuric acid aqueous solution, reaching 10 mA cm at -0.38 V vs. RHE. -2 The current density can reach 10 mA cm at 0.15 V vs. RHE in a 0.5 mol / L sulfuric acid aqueous solution with phenol added. -2 , indicating that phenol reduction is more favorable and has faster kinetics than water reduction.
[0033] like Figure 3 As shown, using the acid-base mixed electrochemical electrolytic cell of Example 1, when phenol is added to 500 mL of 1 mol / L potassium hydroxide aqueous solution in the anode chamber and 500 mL of 0.5 mol / L sulfuric acid aqueous solution in the cathode chamber, the required applied voltage can be significantly reduced to 0.33 V vs. RHE to release 10 mA cm -2 The current density is Figure 4 Shown is the Faradaic efficiency diagram of cyclohexanone, the cathode phenol reduction product. It can be seen that the maximum Faradaic efficiency of 98% can be achieved at -0.15 V vs. RHE, reaching the highest Faradaic efficiency reported in the literature. Figure 5 This is the Faradaic efficiency diagram of benzoquinone, the product of phenol oxidation at the anode. It can be seen that the maximum Faradaic efficiency of 95% can be achieved at 1.30V. Figure 6 The relationship between the reaction time and concentration of phenol reduction to cyclohexanone is shown in Figure 1. The optimization of the reaction time shows that a phenol conversion rate of 98.9% and a cyclohexanone selectivity of 90.3% can be achieved at 60 minutes. Figure 7 The selectivity diagram of phenol reduction to cyclohexanone shows that in the electrochemical reduction reaction of phenol at the cathode, phenol is almost completely converted into cyclohexanone, with a conversion rate close to 100% and a selectivity of over 90% for cyclohexanone. At the same time, in the electrochemical oxidation (EOP) reaction of phenol at the anode, the Faraday efficiency (FE) of generating benzoquinone is benzoquinone ) also remained above 90%. These results fully demonstrate the excellent catalytic ability of the palladium-nickel-boron alloy nanoparticle catalyst supported by nitrogen-doped porous carbon in the selective reduction of phenol to produce cyclohexanone at the cathode and the foam nickel catalyst supported by nickel sulfide-nickel oxide composite nanosheets at the anode in the selective oxidation to produce benzoquinone. Figure 8 Schematic diagram of the stability of the electrochemical electrolytic cell of the present invention. It is found that according to the method of Example 1, the battery can operate stably for 250 hours, but there is a certain fluctuation, which can be restored by refreshing the electrolyte.
Claims
1. A method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol, characterized in that: The method adopts an acid-base mixed electrochemical electrolytic cell, with an alkaline electrolyte as an anolyte, an acidic electrolyte as a catholyte, a nickel foam loaded with nickel sulfide-nickel oxide composite nanosheets as an anode, and a palladium nickel boron nanoparticle alloy with nitrogen-doped porous carbon as a carrier as a cathode. The anolyte and the catholyte are separated by a bipolar membrane, the anion exchange membrane of the bipolar membrane faces the cathode, and the cation exchange membrane faces the anode; phenol is added to the anolyte and the catholyte respectively, so that the anode electrochemically oxidizes the phenol to generate benzoquinone, and the cathode electrochemically reduces the phenol to generate cyclohexanone.
2. The method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol according to claim 1, characterized in that: The cathode electrolyte is a 0.5-2 mol / L sulfuric acid aqueous solution, and the anode electrolyte is a 1-2 mol / L potassium hydroxide aqueous solution.
3. The method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol according to claim 2, characterized in that: The molar ratio of the phenol added to the anolyte to the potassium hydroxide in the anolyte is 1:150-300, and the molar ratio of the phenol added to the catholyte to the sulfuric acid in the catholyte is 1:100-150.
4. The method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol according to claim 1, characterized in that: The bipolar membrane is a Nafion membrane.
5. The method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol according to claim 1, characterized in that: The resistance of the nickel foam loaded with nickel sulfide-nickel oxide composite nanosheets is less than 5Ω, the mass content of nickel in the nickel sulfide-nickel oxide composite nanosheets is 1% to 10%, and the loading amount of the nickel sulfide-nickel oxide composite nanosheets on the nickel foam is 1 to 4 mg / cm 2 .
6. The method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol according to claim 1 or 5, characterized in that: The preparation method of the nickel foam loaded with nickel sulfide-nickel oxide composite nanosheets is as follows: immersing the nickel foam in an aqueous solution containing nickel nitrate, ammonium fluoride and urea, ultrasonicating for 10 to 30 minutes, placing the nickel foam in a reactor for hydrothermal reaction at 90 to 120° C. for 10 to 12 hours, taking out the nickel foam after the reaction, drying it, and calcining it at 300 to 400° C. for 1 to 3 hours in an inert atmosphere, and then placing the calcined product together with a sodium sulfide aqueous solution in a reactor for hydrothermal reaction at 120 to 140° C. for 10 to 14 hours to obtain the nickel foam loaded with nickel sulfide-nickel oxide composite nanosheets; wherein the molar ratio of the nickel nitrate, ammonium fluoride, urea and sodium sulfide is 1:1.5 to 3:0.3 to 1:1 to 2.
7. The method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol according to claim 1, characterized in that: The resistance of the palladium-nickel-boron nanoparticle alloy with the nitrogen-doped porous carbon as a carrier is less than 3Ω, and the loading amount of the palladium-nickel-boron nanoparticle alloy on the carrier is 10wt% to 40wt%.
8. The method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol according to claim 1 or 7, characterized in that: The preparation method of the palladium nickel boron nanoparticle alloy with nitrogen-doped porous carbon as a carrier is as follows: zinc nitrate hexahydrate and 2-methylimidazole are dissolved in methanol respectively, and after they are completely dissolved, the obtained 2-methylimidazole solution is injected into the zinc nitrate hexahydrate solution, stirred at room temperature, precipitated and centrifuged, washed with methanol and deionized water, and then vacuum dried to obtain a ZIF-8 precursor; the ZIF-8 precursor, an ethylene glycol solution of palladium acetylacetonate and an aqueous nickel nitrate solution are mixed, ultrasonically treated to form a uniform solution, and then a sodium borohydride aqueous solution is added under stirring, and heated at 90-140° C. for reaction for 1-2 hours under a nitrogen atmosphere; after the reaction is completed, the palladium nickel boron nanoparticle alloy with nitrogen-doped porous carbon as a carrier is filtered and vacuum dried to obtain the nickel borohydride nanoparticle alloy; wherein the molar ratio of nickel chloride, palladium acetylacetonate and sodium borohydride is 2-3:1:2-3.
9. The method for efficiently co-producing benzoquinone and cyclohexanone based on electrochemical oxidation / reduction of phenol according to claim 1, characterized in that: At a voltage of 1.0 to 1.5 V vs. RHE, phenol is electrochemically oxidized at the anode to generate benzoquinone, and phenol is electrochemically reduced at the cathode to generate cyclohexanone.
Citation Information
Patent Citations
BE706285A
Synchronous and efficient coupling process of cathodic reduction chlorophenol and anodic oxidation phenol
CN109574153A
Method for simultaneously preparing cyclohexanone and benzoquinone by electrocatalytic conversion of phenol with metal supported catalyst
CN114836785A
Electrochemical device and application thereof
CN117210837A
Method of solvent extraction of hydroxybenzene and phenol in aqueous solution
KR1020100127620A
Cited By
Carbon balance quantifying device and method based on phenol high-value conversion
CN121402006A
Carbon balance quantitative device and method based on high-value conversion of phenol
CN121402006B